2014
DOI: 10.3390/nu6125704
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone and Protein Constituents of Lactic Acid-Fermented Soy Milk Combine to Prevent Dyslipidemia in Rats Fed a High Cholesterol Diet

Abstract: A high cholesterol diet induces dyslipidemia. This study investigated whether isoflavone aglycones in lactic acid-fermented soy milk (LFS) improve lipid metabolism in rats fed a high cholesterol diet. Male Sprague-Dawley rats aged seven weeks were fed an AIN-93G diet, a 1% cholesterol diet (a high cholesterol diet), a high-cholesterol diet containing 4% isoflavone extract of LFS (LFS extract diet), a high-cholesterol diet containing 19.4% ethanol-washed LFS (ethanol-washed LFS diet, isoflavone-poor diet), or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
(59 reference statements)
0
14
1
1
Order By: Relevance
“…Additionally, an increase in the amount of isoflavone aglycones in fermented soymilk enhances this lipid metabolism-modulating effect [21]. Although we found that the administration of only isoflavone aglycone fraction from fermented soymilk did not improve lipid metabolism in rats fed a high-cholesterol diet, isoflavone aglycon fraction improved lipid metabolism when given together with soy protein [22]. However, the isoflavone fraction used in our pervious paper, ethanol extract from fermented soymilk, contained both isoflavone aglycones and soy peptides [22].…”
Section: Introductioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Additionally, an increase in the amount of isoflavone aglycones in fermented soymilk enhances this lipid metabolism-modulating effect [21]. Although we found that the administration of only isoflavone aglycone fraction from fermented soymilk did not improve lipid metabolism in rats fed a high-cholesterol diet, isoflavone aglycon fraction improved lipid metabolism when given together with soy protein [22]. However, the isoflavone fraction used in our pervious paper, ethanol extract from fermented soymilk, contained both isoflavone aglycones and soy peptides [22].…”
Section: Introductioncontrasting
confidence: 50%
“…Although we found that the administration of only isoflavone aglycone fraction from fermented soymilk did not improve lipid metabolism in rats fed a high-cholesterol diet, isoflavone aglycon fraction improved lipid metabolism when given together with soy protein [22]. However, the isoflavone fraction used in our pervious paper, ethanol extract from fermented soymilk, contained both isoflavone aglycones and soy peptides [22]. Peptides and protein hydrolysates reportedly exhibit greater bioactivities relative to intact proteins or amino acid mixtures [3] [23].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, in fermented foods such as miso and soy sauce, the sugar is removed to form the aglycone compounds. In a comparative study of aglycones and glycosides, aglycones were found to have better absorption than glycosides and to improve lipid metabolism in liver …”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study of aglycones and glycosides, aglycones were found to have better absorption than glycosides and to improve lipid metabolism in liver. [28,29] Stearidonic acid is an omega-3 polyunsaturated fatty acid (similar to eicosapentaenoic acid and docosahexaenoic acid) that is present in vegetable oils and seaweed. [30] Animal studies have shown that ingestion of stearidonic acid increases the levels of eicosapentaenoic acid, docosapentaenoic acid and docosahexaenoic acid in tissues, [31] which suggests that stearidonic acid intake could be beneficial to health.…”
Section: Discussionmentioning
confidence: 99%